Effects of 5/6 nephrectomy on renal function and blood pressure in mice - Gava, Agata L (e-Century Publishing Corporation, 2012)
Background/Aims: The rat has been the most used experimental animal for studies of cardiovascular and kidney diseases. However, it is notable that there is increasing importance placed on the use of the mouse model to increase understanding of these pathophysiologies. The aim of the present study was to induce chronic kidney disease in a mouse model and to evaluate the resulting changes in blood pressure (BP) and in renal morphology and function. Methods: Adult male C57BL/6 mice underwent 5/6 nephrectomy (5/6 Nx) or a sham operation (Sham). Two weeks later, conscious animals were subjected to a 24-hour urine collection and to a direct measurement of BP. Results: Compared to Sham animals, 5/6 Nx mice showed reduced creatinine clearance (3-fold, p<0.01), proteinuria (1.5-fold, p<0.01) and uremia (4-fold, p<0.01), as well as high blood pressure (~20%, p<0.01). 5/6 Nx animals showed increases in the 24 h urine excretion of Na(+) (2-fold, p<005), K(+) (~2-fold, <0.01) and Ca(2+) (~12-fold). Kidney histology of 5/6 Nx mice also demonstrated glomerular hypertrophy (1.5-fold, p<0.05), mesangial expansion (~40%, p<0.01) and increased glomerular collagen deposition (~30%, p<0.05). Conclusion: Induction of 5/6 nephrectomy in mice for two weeks leads to systemic arterial hypertension and to functional and morphological damage of the remnant kidney, which are considered the main characteristics of chronic kidney disease.